Geographic Information System for the Location Veterinarians Based on Android - Suhendri Widjaja (Universitas Putra Indonesia YPTK Padang, 2021)
Geographic information systems (GIS) have the ability to connect various data at a certain point on the earth, combine them, analyze and finally map the results. The data to be processed in (GIS) is spatial data, which is geographically oriented data and is a location that has a certain coordinate system, as the basis for reference. So that the application (GIS) can answer several questions such as; location, condition, trend, pattern and modeling. This capability is what distinguishes (GIS) from other information systems. The problem in this study discusses the design of a GIS to track the location of veterinarians in the city of Padang. GIS is a concept that can map locations on the earth's surface. The results of its interpretation can be used as information for users in overcoming a problem. The data used in this GIS design is taken from the location of veterinarians in the city of Padang. Gis results provide accuracy in presenting information to users. By building a geographic information system, it is expected to find out where the location of the veterinarians in the city of Padang based can help the android community. So that the public can more easily find out the location of the veterinarians in the city of Padang quickly and accurately which can be accessed via mobile phones (Smartphones). In making this geographic information system, additional application programs used are Android Studio, and other supporting applications